Conidiation in Neurospora crassa: vegetative reproduction by a model fungus - Ruger-Herreros, Carmen; Corrochano, Luis M. (International microbiology, 2020)
Asexual development, conidiation, in the filamentous fungus Neurospora crassa is a simple developmental process that starts with the growth of aerial hyphae. Then, the formation of constrictions and subsequent maturation gives rise to the mature conidia that are easily dispersed by air currents. Conidiation is regulated by environmental factors such as light, aeration and nutrient limitation, and by the circadian clock. Different regulatory proteins acting at different stages of conidiation have been described. The role of transcription factors such as FL, and components of signal transduction pathways such as the cAMP phosphodiesterase ACON-2 suggest a complex interplay between differential transcription and signal transduction pathways. Comparisons between the molecular basis of conidiation in N. crassa and other filamentous fungi will help to identify common regulatory elements.
Published online: 6 June 2019
Gesehen am 01.04.2020